Dewdrop - O'Neill, Katie (Cartoonist) (Oni Press, 2020)
"It's time for the annual pond sports fair. Dewdrop the axolotl can't wait to cheer on his friends. But as the big day gets closer and his friends get nervous, will he be able to remind them that doing their best is the most important part?"--Back cover.